Flotillin-1 Interacts With and Sustains the Surface Levels of TRPV2 Channel - Hu, Juan; Gao, Yue; Huang, Qian; Wang, Yuanyuan; Mo, Xiaoyi; Wang, Peiyu; Zhang, Youjing; Xie, Chang; Li, Dongdong; Yao, Jing (Frontiers in Cell and Developmental Biology, 2021)
Transient receptor potential vanilloid subtype 2 (TRPV2) channel is a polymodal receptor regulating neuronal development, cardiac function, immunity and oncogenesis. The activity of TRPV2 is regulated by the molecular interactions in the subplasmalemmel signaling complex. Here by yeast two-hybrid screening of a cDNA library of mouse dorsal root ganglia (DRG) and patch clamp electrophysiology, we identified that flotillin-1, the lipid raft-associated protein, interacts with TRPV2 channel and regulates its function. The interaction between TRPV2 and flotillin-1 was validated through co-immuoprecipitation in situ using endogenous DRG neurons and the recombinant expression model in HEK 293T cells. Fluorescent imaging and bimolecular fluorescence complementation (BiFC) further revealed that flotillin-1 and TRPV2 formed a functional complex on the cell membrane. The presence of flotillin-1 enhanced the whole-cell current density of TRPV2 via increasing its surface expression levels. Using site-specific mapping, we also uncovered that the SPFH (stomatin, prohibitin, flotillin, and HflK/C) domain of flotillin-1 interacted with TRPV2 N-termini and transmembrane domains 1–4, respectively. Our findings therefore demonstrate that flotillin-1 is a key element in TRPV2 signaling complex and modulates its cellular response.